Development of the graphical-analytical method for calculating electric load at civilian objects - Bondarchuk, Anatolii (Eastern-European Journal of Enterprise Technologies, 2017)
The calculation method is proposed for electric load at civilian objects, whose novelty, in contrast to determining in line with the acting standards, is in the improvement of its determining accuracy. This will be made possible by developing chart models of the load of electrical receivers, their synthesis at the inputs of civilian objects. The original information for modeling is obtained in advance by measuring chart parameters of similar functioning systems of power supply. The implementation of the proposed method would bring down the cost of material and energy resources. We constructed theoretical and actual mathematical models of their dynamics using the function «cspline (x,y)» embedded in MathCAD, extending the interpolation curve with a cubic parabola. We evaluated the errors of theoretically calculated, relative to actual, specific electric load at civilian objects, under conditions of the city of Odessa. Using the graphic-analytical method would improve accuracy in the calculation of electric load by 1.5–3.5 times compared with that determined in line with the standards. This could save energy resources, capital expenditures on the construction and operation of power supply systems.